lidA–leben in der Arbeit. German cohort study on work, age and health - Angela Rauch; Anja Burghardt; Johannes Eggs; Anita Tisch; Silke Tophoven (Journal for Labour Market Research, 2015)
– The aim of the study 'lidA-leben in der Arbeit. German Cohort Study on Work, Age and Health' is to provide a database that enables the investigation of the relationship between work, ageing and health. lidA focuses on two birth cohorts of German baby boomers, born in 1959 and 1965. The longitudinal design of the study allows not only the differentiation between age groups but also identification of cohort and period effects. For this purpose, employees of the two cohorts are interviewed repeatedly at intervals of 3 years. The content of the survey is divided into three thematic fields: The first field concentrates on their current work situation and occupation and contains questions on work environment and individual evaluation of job demands. The second thematic field includes a range of questions on the health status of the interviewees. Additionally, a hand-grip strength test is conducted as an objective indicator for long-term development of muscle strength. The last set of survey questions goes into more detail on the household and socio-demographic characteristics of the respondents. This article gives an overview of the currently available first two waves of the lidA panel survey. The article is structured as follows. After an introduction, the main aims of the study are discussed. The subsequent sections describe the research and sampling design as well as the content of the survey. The paper concludes with an outlook, information on data access and the prospects of future research on the basis of lidA.
Keywords: C8; I10; J28; 330; IAB-Datensatz Leben in der Arbeit; Kohortenanalyse; Altern; Berufsverlauf; Gesundheitszustand; Längsschnittuntersuchung; altersspezifische Faktoren; Befragung; Forschungsmethode; Stichprobenverfahren; Fragebogen; Datenzugang; ältere Arbeitnehmer; Arbeitsbedingungen